PENYEDIAAN DAN PEMELIHARAAN SARANA DAN PRASARANA PARIWISATA OLEH DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN KUANTAN SINGINGI TAHUN 2013-2014 - Ogi Seftiawan; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine determine the planning process in the provision and maintenance of facilities and tourism infrastructure in Kuantan Singingi and knowing the obstacles in the provision and maintenance of facilities and tourism infrastructure in Kuantan Singingi. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Facilities and infrastructure attractions Niagara Falls Thunder Gemurai and seven levels Batang Koban incomplete and means that there is also in no circumstances be maintained so it can not be used as a toilet ,, there kondisisnya is damaged, the door has been dated and can not be used again , as well as locker rooms, condition was broken so visitors who came difficult to find a place to change clothes and places of worship / prayer room less kept clean, especially the floors were dirty and no equipment to pray like, sejadah, mukenah, and other-other. During this time there is no effort from the parties involved to make improvements of facilities and infrastructure that has suffered such damage The conclusion that the provision and maintenance of Infrastructures in Kuantan Singingi Tourism Attraction in Niagara Falls Thunder Gemurai and seven levels Batang Koban incomplete and not well maintained. Obstacle to the provision and maintenance of facilities and infrastructure in Kuantan Singingi Tourism is of limited funds, human resources, ie, not all employees in the department of culture youth and sports tourism Kuantan district Singingi the educational background in tourism and a lack of community support around. Keywords: Provisioning, Maintenance, Facilities and Infrastructure Tourism.